Characteristics of Shale Pores and Surfaces and Their Potential Effects on the Fluid Flow From Shale Formation to Fractures - Li, Xu; Cai, Jingong; Gao, Bo; Long, Shengxiang; Feng, Dongjun; Peng, Zeyang; Guo, Benqiang (Frontiers in Earth Science, 2021)
Fluid flow is critical for the efficient exploitation of shale resources and can be split into two stage: the flow in the artificial fractures and more importantly, the flow from shale formations to the artificial fractures. In this paper, X-ray diffraction, N2 adsorption, Mercury intrusion and ethylene glycol monoethyl ether (EGME) adsorption were conducted on the shales collected from the Es3middle, the Es3lower and the Es4upper sub-member in the Dongying Sag to reveal the potential effects of the characteristics and properties of pores and surfaces on the fluid flow in shale formations. The results indicate that: (1) The shales from the Es3middle and the Es3lower contain more I/S and detrital minerals but less illite and carbonate minerals than those of the Es4upper. (2) The shales from the Es3middle and the Es3lower are mainly composed of smaller pores present larger surface areas and lead to the steeper slope between Brunauer-Emmett-Teller specific surface area (BET-SSA) and pore volumes. (3) Clay minerals mainly contribute to pore development and carbonate minerals inhibit pore development. All kinds of surface areas (especially inner surface area) are sourced by clay minerals, while I/S and illite present opposite effect. (4) Pore size and surface properties affect significantly on the fluid flow in shale formations. The shales from the Es4upper are the favorable interval for shale oil accumulation and flow, especially for the shales with depth ranges of 3360~3410 m, which possess high carbonates, illite and total organic carbon (TOC) content, low clay mineral content, large pore volume, high large pore content and small surface areas. Additionally, fluid composition need to be paid more concern in the future.